Analisis Perbedaan Tingkat Kepuasaan Pasien terhadap Pelayanan Perawat di Rawat Inap VIP dan Bangsal - Ulfah Hidayah Almadany; Siti Zahara Nasution; Isti Ilmiati Fujiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to look at the analysis of the level of patient satisfaction with nurse services at VIP (Very Important Person) inpatient care and Wards at Padangsidimpuan City General Hospital. This research method is analytic with a cross-sectional approach. This research began to be carried out in September 2022 - March 2023 in the VIP Inpatient Ward at Padangsidimpuan City General Hospital. The study sample of VIP inpatients was 96 people and Ward was 96 people with sideways purposive technique. Univariate and bivariate data analysis with Chi-square test. The results showed that in the VIP room, the most dissatisfied were 50 people (52.1%) and the wards were the most dissatisfied with 76 people (79.2%). The results of the chi-square test obtained a p-value â‰¤ 0.05, so there was a significant relationship between VIP and Ward patient satisfaction with the dimensions of Patient Satisfaction at Padangsidimpuan City General Hospital. In conclusion, there is a significant relationship between VIP and Ward patient satisfaction with the dimensions of Patient Satisfaction at Padangsidimpuan City General Hospital. Keywords: Nurse Service, Satisfaction Level, VIP, Ward.